THE RELATIONSHIP BETWEEN PRINCIPAL COMPETENCE AND STIMULUS TEACHER COMPETENCE AT TK AISIYAH 84 CENGKARENG WEST JAKARTA - Nurlaelah, Nurlaelah; Imamah, Imamah (Journal of Early Childhood Education (JECE), 2023)
The background of this research is that the principal's leadership is an important stimulus and management factor. In addition, the competence of stimulus teachers is still not maximal in fulfilling academic qualifications. The purpose of this study was to determine the relationship between the principal's leadership competence and the competence of the stimulus teacher. The methodology in this study used quantitative with a simple regression technique, while the data collection method used a questionnaire. The sample used 25 teachers selected randomly. The analysis technique uses SPSS which is interpreted descriptively quantitatively. The findings show that the leadership of the kindergarten principal has a positive relationship with the competency of the stimulus teacher, the ability of the principal to lead can mobilize all educators effectively and efficiently. The important thing is to motivate educators to apply student-oriented learning and character-building.